Theabrownin ameliorates liver inflammation, oxidative stress, and fibrosis in MCD diet-fed C57BL/6J mice - Zhen, Qingcai; Liang, Qijian; Wang, Hongchun; Zheng, Yan; Lu, Zhongting; Bian, Chunyong; Zhao, Xiulan; Guo, Xin (Frontiers in Endocrinology, 2023)
Introduction Nonalcoholic steatohepatitis (NASH), also known as metabolic steatohepatitis, is a clinical syndrome with pathological changes like alcoholic hepatitis but without a history of excessive alcohol consumption. NASH is closely related to metabolic disorders such as obesity, insulin resistance, type 2 diabetes mellitus, and hyperlipidemia. Its main characteristics are hepatocyte steatosis with hepatocyte injury and inflammation. In severe cases, it can develop into liver cirrhosis. At present, there is no special treatment for NASH. Theabrownin (TB) is the main pigment substance in fermented tea. Theabrownin has beneficial effects on lipid metabolism and intestinal flora. However, the effect of theabrownin on NASH has not been studied. Methods This study was aimed at exploring the effects of theabrownin from Fuzhuan brick tea on NASH. 8-week-old mice were randomly assigned to three groups and fed with chow diet (CD), methionine and choline sufficient (MCS) diet (MCS Ctrl), which is a Methionine/choline deficient (MCD) control diet, and MCD diet. After 5 weeks of feeding, the MCD group mice were randomly divided into two groups and were gavaged with double distilled water (MCD Ctrl) or theabrownin (MCD TB) (200mg/kg body weight, dissolved in double distilled water) every day for another 4 weeks respectively, while continuing MCD diet feeding. Results We found that theabrownin treatment could not improve liver mass loss and steatosis. However, theabrownin ameliorated liver injury and decreased liver inflammatory response. Theabrownin also alleviated liver oxidative stress and fibrosis. Furthermore, our results showed that theabrownin increased hepatic level of fibroblast growth factor 21 (FGF21) and reduced the phosphorylation of mitogen-activated protein kinase p38 in MCD diet-fed mice.